The Urge for ‘X-treme’: Super-Human Syndrome Followed by the Morality of Viciousness - Taslim, Israt (EAST WEST JOURNAL OF HUMANITIES, 2015)
X-treme is considered to be a new popular phenomenon which brings out the hidden fantasy of any normal human being, to test every possible limitation till the ultimate extent. Though the practice of extreme is considered as villainous and not easily acceptable by the society, it is the human fantasy to go to X-treme in order to be included in the minority of being superhuman. In our postmodern world aesthetics get more priority than ethics when media visualize the inner fantasy of violence in reality as a spectacle for the audience. This media increases the urge of being superhuman, while being human is too cliché. Now, X-treme has become so important to bring every possible limit out of people that they do not bother whether it is related to morality or not. It is obvious to find a superhero against the features of postmodernism because he is unmovable from the fixed convention of being good and not allowing the X-treme. That morality makes a superhero limited and stereotyped with all cliché traits of being inside the boundary. On the other hand, villains or anti-hero can possess the X-treme power and exhibit the extremity desired by the audience. So, villains are more appreciable than heroes because they become the example of living larger than life in this lifetime. The clean line of being good or bad is dead – thanks to postmodernism which justifies the practice of going to every possible limit of X-treme. When the postmodern ethics is already compromised, a new kind of ethics emerges in human mind. That ethics is more than personal which does not bother to maintain the universal ethics that is predetermined or enforced social ideology and silences the moral impulse of the individuals. When that personal ethics might also be the result of the enforced ideology, a free mind can create its own morality by stepping out of the influence of any kind of social ideology.